Geriatric Workforce Capacity: A Pending Crisis for Nursing Home Residents - Lee, Wei Chen; Sumaya, Ciro V. (Frontiers in Public Health, 2013)
Introduction: The nursing home (NH) population in the U.S. has grown to 1.6 million people and is expected to double by 2030. While 88.3% of NH residents are over 65, the elders aged 85 and more have become the principal group. This demographic change has increased the already high rates of chronic diseases and functional disabilities in NH residents. Methods: This study reviewed the supply of geriatricians in addressing the growing healthcare needs of NH residents. Results: English-written articles between 1989 and 2012 were reviewed. Trend data demonstrate that the geriatrician workforce has decreased from 10,270 in 2000 to 8,502 in 2010. Further, the pipeline analysis of physicians projected to receive board certification in geriatrics (and maintain this certification) indicates a worsening of the already insufficient supply of geriatricians for this vulnerable population. Conclusion: Strategies to attract and maintain a geriatrician workforce are imperative to avert a mounting crisis in the geriatric care in NH and, by extension, other living settings.